Synthetic biology to engineer bacteriophage genomes - Costa, Ana Rita (2024)
Recent advances in the synthetic biology field have enabled the development of new molecular biology techniques used to build specialized bacteriophages with new functionalities. Bacteriophages have been engineered toward a wide range of applications, including pathogen control and detection, targeted drug delivery, or even assembly of new materials. In this chapter, two strategies that have been successfully used to genetically engineer bacteriophage genomes will be addressed: the bacteriophage recombineering of electroporated DNA (BRED) and the yeast-based phage-engineering platform.